Pleistocene cetacean fossils from the coastal plain of Rio Grande do Sul in southern Brazil. Issue 3 (3rd July 2021) - Carrasco, Thayara Silveira; Buchmann, Francisco Sekiguchi
Abstract: Cetacean ear bones are useful for palaeontological studies because it is possible to identify most species based on their gross morphology, and thus glean information about past occurrences and distributions. This study describes cetacean tympanic bullae and periotics preserved in Middle–Late Pleistocene coastal barrier systems from Rio Grande do Sul in southern Brazil. The specimens were collected ex situ on the modern beach, and reveal the presence of the Franciscana dolphin, Pontoporia blainvillei, an indeterminate delphinid, the rorqual whale, Balaenoptera, and right whale, Eubalaena . Given the current diversity of dolphins and whales in the Atlantic Ocean, these fossils suggest that the reported diversity of Pleistocene cetaceans is probably underestimated. The barrier systems of Rio Grande do Sul are the only Brazilian deposits that have preserved Pleistocene cetacean remains to date. Thayara Silveira Carrasco * [thayaracarrasco@gmail.com ], Laboratório de Estratigrafia e Paleontologia and Programa de Pós-graduação em Biodiversidade de Ambientes Costeiros, Instituto de Biociências, Campus do Litoral Paulista, Universidade Estadual Paulista, 11330-900 São Vicente, SP, Brazil; Francisco Sekiguchi Buchmann [paleonchico@yahoo.com.br ], Laboratório de Estratigrafia e Paleontologia, Instituto de Biociências, Campus do Litoral Paulista, Universidade Estadual Paulista, 11330-900 São Vicente, SP, Brazil.